Variability of the Interplanetary Magnetic Field as a Driver of Electromagnetic Induction in Mercury's Interior. Issue 10 (6th October 2021) - Zomerdijk‐Russell, S.; Masters, A.; Heyner, D.
Abstract: Mercury's magnetosphere is a unique and dynamic system, primarily due to the proximity of the planet to the Sun and its small size. Interactions between solar wind and embedded interplanetary magnetic field (IMF) and the dayside Hermean magnetosphere drive an electric current on the system's magnetopause boundary. So far, electromagnetic induction due to magnetopause motion in response to changing external pressure has been used to constrain Mercury's iron core size. Here we assess the impact a changing IMF direction has on the Hermean magnetopause currents, and the resulting inducing magnetic field. Observations made by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft during dayside magnetopause boundary crossings in the first "hot season, " are used to demonstrate the importance of the IMF direction to Mercury's magnetopause currents. Our 16 boundary crossings show that introduction of external IMFs change the magnetopause current direction by 10° to 100°, compared to the case where only the internal planetary field is considered. Analytical modeling was used to fill in the bigger picture and suggests for an east‐west reversal of the IMF, typical of the heliospheric current sheet sweeping over Mercury's magnetosphere, the inducing field at Mercury's surface caused by the resulting magnetopause current dynamics is on the order of 30% of the global planetary field. These results suggest that IMF variability alone has an appreciable effect on Mercury's magnetopause current and generates a significant inducing magnetic field around the planet. The arrival of the BepiColombo mission will allow this response to be further explored as a method of probing Mercury's interior. Plain Language Summary: Mercury has a large iron core, in which a magnetic field is produced. Determining the precise size of this core and the composition of Mercury's interior are key to developing our understanding of the terrestrial planet's formation and evolution and, therefore, the mechanisms involved in the formation of our solar system. Changes to the sheet of electric current that shields Mercury from the stream of charged particles ejected from the Sun can be used as a natural metal detector to reveal properties of Mercury's subsurface. Through observational data and modeling of the interactions between Mercury's magnetic field and the external magnetic field generated by the Sun, we assess a way in which this electric current sheet can be altered. Our results showed that variability in the orientation of the external magnetic field from the Sun has an appreciable impact on Mercury's shielding electric current sheet. The arrival of the BepiColombo mission in 2025 will allow this response to be further explored as a method of probing Mercury's interior. Key Points: We assess the impact of a changing interplanetary magnetic field (IMF) direction on Mercury's magnetopause current and resulting inducing field We show that variability of the IMF direction alone has an appreciable effect on Mercury's magnetopause currents This response, and BepiColombo's arrival, will allow inducing fields to be further explored as a method of probing Mercury's interior